Introduction of dairy goats in a rural smallholder setting in Burundi: Milk production parameters of crossbreds in different production systems - Schmidt, U.; Jauner, H. (1989)
A crossbreeding program between the Small East African goat and the Alpine goat has been implemented in Burundi (1980) to improve milk production from smallholder goats. In the breeding center purebred Alpines had lactation yields of 432.81 to 480.9l in 1st to 3rd lactations. R1-crossbreds (75% Alpine) produced 264.0l in the first lactation and 355.8l in the second lactation. Lactation yield of F1-crossbreds was 198.51 and 236.31 in lactations 1 and 2. The lactation period was clearly shorter for F1 (203 and 208 days) than for Alpine and R1 (238.5 days to 265.1 days). In smallholder conditions the results for F1 were 261.4l (including milk consumed by the kids for the 1st to 3rd lactation) or 79.1 1 of commercialized dairy milk surplus. For R1 (75% Alpine) total milk yield was 215.4l (1st lactation only) or 109.4% of commercialized milk. Lactation period of both F1 and R1 was shorter in smallholder conditions, than it was in the breeding center.